Price Perception and Brand Affect Purchase Decision - Ridwan Ridwan (Siber Nusantara of Economic and Finance Review, 2024)
This study aims to analyze the influence of price and brand perception on consumer purchasing decisions based on a literature review. Price perception and brand strength are two important factors that can influence consumer behavior in making purchasing decisions. Through a literature review of various relevant studies, this study found that high price perception tends to increase consumer trust and brand loyalty, which ultimately drives positive purchasing decisions. In addition, a strong brand can increase the perception of value at price and provide a competitive advantage in the market. The results of this study indicate that both product price and brand play an important role in influencing consumer purchasing decisions, so companies need to integrate price perception improvement strategies and effective brand management to improve sales performance.